THE USE OF PROJECT-BASED LEARNING IN THE CLASSROOM - Egamova , Nigora Ustamirzayevna (Innovative Development in Educational Activities, 2023)
The following article highlights of ausingproject-based learning in the classroom. Author made a imperic research on this issue. The application of the project method in English lessons is being considered language in elementary school. There is one types of projects. It is educational. It is proved that the project method is a method that allows organizing the educational activities of younger schoolchildren, forming universal educational activities, developing the personality of each participant of the project. Special attention is paid to the peculiarities of organizing joint educational activities of students in the project in particular, the organization of group interaction.